Fashionopolis : the secrets behind the clothes we wear - Thomas, Dana, 1964- (Dial Books for Young Readers, 2022)
Provides an overview of the fashion industry for young readers, designed to help them understand where the clothes they wear come form and their impact on the environment. From design to production, follows how clothes are made, explores the history of clothing design and production, explains the creative theft, low-wage workers, and pollution caused by fast fashion.